Detailed surface analysis of V‐defects in GaN films on patterned silicon(111) substrates by metal–organic chemical vapour deposition. Issue 3 (31st May 2019) - Gao, Jiang-Dong; Zhang, Jian-Li; Zhu, Xin; Wu, Xiao-Ming; Mo, Chun-Lan; Pan, Shuan; Liu, Jun-Lin; Jiang, Feng-Yi
Abstract : This is a detailed study on a common type of defect in GaN materials. The data and results are important for the growth and application of GaN materials. Abstract : The growth mechanism of V‐defects in GaN films was investigated. It was observed that the crystal faces of both the sidewall of a V‐defect and the sidewall of the GaN film boundary belong to the same plane family of, which suggests that the formation of the V‐defect is a direct consequence of spontaneous growth like that of the boundary facet. However, the growth rate of the V‐defect sidewall is much faster than that of the boundary facet when the V‐defect is filling up, implying that lateral growth of planes is not the direct cause of the change in size of V‐defects. Since V‐defects originate from dislocations, an idea was proposed to correlate the growth of V‐defects with the presence of dislocations. Specifically, the change in size of the V‐defect is determined by the growth rate around dislocations and the growth rate around dislocations is determined by the growth conditions.